PELAKSANAAN PEMILIHAN UMUM DALAM SEJARAH NASIONAL INDONESIA PADA MASA ORDE BARU DAN REFORMASI - Sofyan Kriswantoni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2018)
Muhammadiyah is one of the Islamic organizations in Indonesia. The existence of Elections in Indonesia's national history were carried out several times, namely during the Old Order era, namely 1955, the New Order period 1971, 1977, 1982, 1987, 1992 and 1997. Elections for a democratic country like Indonesia are very important because elections are a channel for people's aspirations. Elections that have been held in Indonesia have their own characteristics with differing democratic levels, so the truth of the argument needs to be proven in order to obtain an accurate answer. The results obtained from this study that the implementation of general elections in the Old Order period can already be categorized as democratic elections, with the many parties participating in the general election signifying the existence of freedom in political life, whereas during the New Order the democratic period faded along with the power of the Suharto regime which always curbed the political life of the Indonesian nation, the implementation of the general election during the Reformation especially the 2004 general election was more democratic because the implementation of the election could represent the aspirations of the people especially with the electoral system which was different from the previous election because with a combination of district and proportional systems then the people can know and know what people's representatives will like to channel their aspirations.